Characterization of root-knot nematode responsive and root-specific promoter containing PIN domain from Arabidopsis thaliana (L.) Heynh. - Kumar, Anil; Joshi, Ila; Kohli, Deshika; Satheesh, V; Abdin, M.Z.; Sirohi, Anil; Srinivasan, R; Jain, P.K. (The Indian Journal of Genetics and Plant Breeding, 2016)
Root-knot nematodes (Meloidogyne incognita) are obligate plant parasites, causing significant economic loss, that alter expression of host genes in order to establish and maintain their feeding sites in the roots of host plants. In the present study, a nematode-responsive-root-specific gene (AT1G26530) was identified which expressed in roots of Arabidopsis thaliana after nematode infection. Quantitative RT-PCR analysis of this gene revealed maximum ( 2.58 fold) up-regulation at 21 days post inoculation of nematode. A 1580 bp region upstream of the translational start site of AT1G26530 was isolated and transformed into Arabidopsis through floral dip method. On analysis of Arabidopsis transgenic plants harboring AT1G26530 prm::GUS fusion, reporter gene expression was seen exclusively in galls after nematode inoculation. Interestingly, strong GUS activity was observed at early stages of nematode infection, starting from 14 days and was sustained up to 30 days post inoculation. Furthermore, 85 to 93 % galls exhibited GUS activity in the nematode feeding sites. The specificity of the activity of the AT1G26530 promoter, in terms of nematode-responsiveness and rootspecificity, makes it a suitable candidate to express dsRNA of nematode genes and engineer plants with resistance against root-knot nematodes using HD-RNAi technology.